ANALISIS PERBANDINGAN ISU JAWATAN KHALIFAH ATAU IMAMAH ANTARA AHLU SUNNAH DENGAN SYI’AH - Maafi Husin; Muhammad Hilmi Jalil; Zakaria Stapa; Jawiah Dakir (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2020)
AbstractThe position of caliph after the death of the Prophet SAW is a problem faced by Muslims in the past, who is entitled to hold the position of caliphate after the death of the Prophet SAW, whether Abu Bakr, Umar, Uthman or Ali r.a. therefore, this writing is a comparative analysis of the issue of the position of caliph or imamah between Sunnis and Shiites. This study discusses the evidence that comes from the verses of the Qur'an that is the verse of al-Tabligh, this verse is used as a weapon of da'wah for the Shiites because there are several hadiths that interpret the verse, one of which is the hadith based on referring to words Abu Sa'id al-Khudri ra, that this verse was revealed regarding Ali bin Abi Talib ra, led to his appointment as caliph of the Muslims in a place called Ghadir Khum. This appointment is known as the Ghadir Khum sermon. However, there are some problems in the methodology of interpreting the verses of the Qur'an, this methodology of interpretation needs to be studied and analyzed because it involves the words of Allah SWT and a very big issue that is the position of caliph or imamah after the death of the Prophet Muhammad SAW. The objective of the study is also to assess the extent to which the methodology of the interpretation of the verse is true by comparing propositions sourced from Sunnis and Shiites. The research methodology is a library study, this data analysis method will explain the analysis techniques that will be used such as comparative studies, content analysis, data validation and so on. This study found that the Shiite methodology in the interpretation of the verse of al-Tabligh is inaccurate in terms of the actual standard of interpretation because the verse does not show the specificity of the appointment of Ali ra as the caliph of Muslims, while the hadith that interprets the verse as the Prophet SAW said -said Abu Sacid al-Khudri, ra has a weak Sanad narration, Atiyah is also well known for relying on Shi'iyyat narrations because he is a Shiite.